2017
DOI: 10.5897/ajb2016.15768
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of traditional sweet cassava accessions from Southern of Minas Gerais State, Brazil, using microsatellite markers

Abstract: Sweet cassava is a food culture of great importance because it is a source of nutrition and energy for millions of people in tropical and sub-tropical regions. For that reason, genetic diversity and population structure studies are necessary in order to obtain more information regarding the evaluated genotypes, reassuring their use in future breeding programs. The objective of this study was to evaluate the genetic diversity and population structure of 51 traditional sweet cassava accessions collected in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The accumulated variation in the first two principal coordinates was low, as in the study by Sousa et al (2017), that analyzed cassava varieties and identified only 17.84% of the variation in two coordinates and, as in the present study, were not able to detect genetic structure corresponding to the cyanogenic content of the varieties, attributing this to misidentification of "sweet" or "bitter" varieties and possible mixture of accessions during clonal propagation (on farm and ex situ). However, Costa et al (2013) and Gonçalves et al (2017) when evaluating "sweet" cassava managed to explain much of the variation in two coordinates (53.25% and 48.21%, respectively). Comparing the Bayesian analysis data with PCoA, the observed dispersion supported the establishment of the two groups identified by the Bayesian analysis, emphasizing the grouping of the duplicated accessions and also showing no correspondence either with cyanogenic content of the accessions and with the genotypes collection site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulated variation in the first two principal coordinates was low, as in the study by Sousa et al (2017), that analyzed cassava varieties and identified only 17.84% of the variation in two coordinates and, as in the present study, were not able to detect genetic structure corresponding to the cyanogenic content of the varieties, attributing this to misidentification of "sweet" or "bitter" varieties and possible mixture of accessions during clonal propagation (on farm and ex situ). However, Costa et al (2013) and Gonçalves et al (2017) when evaluating "sweet" cassava managed to explain much of the variation in two coordinates (53.25% and 48.21%, respectively). Comparing the Bayesian analysis data with PCoA, the observed dispersion supported the establishment of the two groups identified by the Bayesian analysis, emphasizing the grouping of the duplicated accessions and also showing no correspondence either with cyanogenic content of the accessions and with the genotypes collection site.…”
Section: Resultsmentioning
confidence: 99%
“…The use of molecular markers is an efficient tool to differentiate accessions, to identify redundancies and to select genotypes with characters of interest (COSTA et al, 2013;MOURA et al, 2013;GONÇALVES et al, 2017;SOUSA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Figura 4 -Dendrograma com os 24 genótipos de Manihot esculenta obtido pelo método UPGMA, utilizando-se a distância de Rogers modificada (Wright, 1978) com 10 locos microssatélites Fonte: Resultados da Pesquisa A maior distância (0,7246) foi observada entre os genótipos P005 Amarela e P003 Chico Anjo. Genótipos com grande divergência podem ser empregados em programas de melhoramento como progenitores, para produzir híbridos altamente heteróticos (GONÇALVES et al, 2017). A menor distância (0,1581) entre os indivíduos geneticamente distintos foi observada em dois pares de genótipos, sendo os genótipos Rasgadinha e P001 Amarelinha Talo Vermelho e P007 Manteiguinha e P001 Amarelinha Talo Vermelho.…”
Section: Resultsunclassified
“…Therefore, it is important to carry out studies to identify duplicated accessions and assess the genetic diversity within accessions in order to provide breeding programs with unique genotypes [1,13]. An assessment of cassava genetic diversity has been carried out using morphological descriptors [14,15] and molecular markers [1,[16][17][18]. However, morphological descriptors are known to be affected by the interaction between genotype and environment.…”
Section: Introductionmentioning
confidence: 99%